2019
DOI: 10.1016/j.amsu.2019.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Rare presentation of primary varicella zoster as fatal fulminant hepatitis in adult on low-dose,short-term steroid: Case report

Abstract: BackgroundVaricella zoster virus presents clinically as primary (chickenpox) or secondary (herpes zoster) infection. Cutaneous and extracutaneous dissemination may occur, usually in immunocompromised patients. VZV hepatitis that progresses to fulminant hepatic failure is very rare and fatal. To the best of our knowledge, 9 cases have been reported to date, of which 7 were in immunocompromised adults, and only one patient was on short duration steroid therapy.Presentation of caseWe present a 26-year old man who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Hepatic involvement in varicella showed symptoms of vague epigastric pain, nausea, vomiting, and a possible increase in liver volume [11] . An increase in liver function test panel is expected, a couple of studies reported AST raised higher than ALT along with the increase of INR and bilirubin [12,13] . Risk factors for complications in varicella are newborns, adults, immunocompromised, males, smokers, and pregnant women.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hepatic involvement in varicella showed symptoms of vague epigastric pain, nausea, vomiting, and a possible increase in liver volume [11] . An increase in liver function test panel is expected, a couple of studies reported AST raised higher than ALT along with the increase of INR and bilirubin [12,13] . Risk factors for complications in varicella are newborns, adults, immunocompromised, males, smokers, and pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies showed clinical improvement, but some mentioned at risk of superinfections [16,17,18,19] . Reports showed that use of steroids prior varicella infection might cause fulminant hepatitis [12,13] . Nevertheless, the use of steroids remains a clinical decision [19] .…”
Section: Radiologic Chest X-ray Features Of Varicellamentioning
confidence: 99%
“…Normally, we tend to focus more on immunocompromised people because severe varicella mostly occurs in children and immunodeficient people [12]. However, in recent years, it has been reported that adult varicella patients with normal immune function have serious complications, such as acute respiratory distress, liver failure and cerebral venous sinus thrombosis [13][14][15][16]. Moreover, as adults typically do not voluntarily vaccinate against varicella, varicella infections in adults are likely undervalued and understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis is another complication that should be identified promptly in adults with primary varicella [ 25 ]. It is essential to consider that immunosuppressed patients have a higher risk of this complication, usually presenting poor clinical outcomes [ 25 ]. However, mild transaminase elevation has been described even in healthy individuals with varicella [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention should be given to patients with two-fold or three-fold the upper normal rank value. These patients have a higher risk of hepatitis-associated complications such as disseminated intravascular coagulation (DIC) or gastrointestinal bleeding [ 25 ]. Of note, cases of fulminant acute hepatic failure, although rare, have been reported.…”
Section: Discussionmentioning
confidence: 99%